PLANNING AND ORGANIZATION OF AUDIT OF CAPITAL INVESTMENTS IN JOINT-STOCK COMPANIES - Jumamurodov To’libay Eldashbaevich (INTERNATIONAL JOURNAL OF RESEARCH IN COMMERCE, IT, ENGINEERING AND SOCIAL SCIENCES ISSN: 2349-7793 Impact Factor: 6.876, 2023)
At "Uzbekkogzi" JSC, audits are conducted once a year based on the planned rules. We would like to share our thoughts on the procedure for formalizing the results of capital investments and improving its specific features while analyzing the company’s audits. Since the investigation of the company’s total capital investment is confidential, we have taken a general approach in order not to publicize it.